Pengaruh Program Loyalitas Digital Alfagift Terhadap Loyalitas Pelanggan Alfamart (Studi Pada Konsumen Di Store Alfamart) - Mohammad Febri; Sasi Yunia Aryanti; Putri Husnaini; Ratna Dewi Setiawati; Rifkhan Rifkhan (CV. ITTC INDONESIA, 2026)
This study examines the effect of the Alfagift digital loyalty program — through its feature ease of use (X1), service benefits (X2), and reward program (X3) — on customer loyalty (Y) at Alfamart. Sales data from the observed store showed Alfagift’s contribution consistently at 11–15%, well below the corporate target of 25%. A quantitative associative-causality approach was employed with 100 respondents selected through purposive sampling and analyzed using multiple linear regression (IBM SPSS). All 40 questionnaire items were valid (r-hitung 0.688–0.834 > r-tabel 0.195) and highly reliable (Cronbach’s Alpha 0.954–1.000). Classical assumption tests confirmed normality, no multicollinearity, and no heteroscedasticity. The regression equation is Y = −3.481 + 0.309X1 + 0.289X2 + 0.429X3. Partial tests (Uji t) show feature ease of use (t = 1.993, p = 0.049) and reward program (t = 3.088, p = 0.003) significantly affect loyalty, while service benefits (t = 1.610, p = 0.111) do not. Simultaneously (Uji F), F = 33.542 (p = 0.000), confirming H4. The coefficient of determination R² = 0.512 indicates 51.2% of variance in loyalty is explained by the three variables. Reward programs emerged as the most dominant driver of customer loyalty.